The Lumwana Copper Prospect in Zambia - McGregor, James Archibald (Rhodes University, Faculty of Science, Department of Geology, 1965)
The Lumwana copper orebody is situated 170 miles west of the Copperbelt. It is stratiform and occurs in schists regarded as part of the Katanga System older than the lower-most Copperbelt quartzite. The discovery of copper at the Lumwana Prospect was a text book example of the success of the R.S.T. Mines Services Limited prospecting techniques. These include partial geochemical analyses of soil and drainage samples, pitting, drilling and radiometric, self potential, magnetic, resistivity and induced polarization methods of geophysical exploration. The copper-bearing formations at the Lumwana Prospect occur in the inverted limb of a great recumbent fold within the Mombezhi Dome. Three periods of folding are recognized from the study of regional foliations and lineation, and the attitude of fold elements in individual folds. Each period of folding is regarded as a major pulse in the Lufilian Orogeny. The first-formed folds are isoclinal and have axial planes which strike at 160°, and dip southwest at 15°; the plunge is 11° in a direction 212° . The formation of first folds was accompanied by thrust faulting and the development of nappe structures including the great Lumwana recumbent fold. The second folds have axial planes which strike at 170° and dip west at 44°, the plunge is 12° in a direction of 192°, and the folds tend to be overturned. The third folds cut across the earlier folds at variable angles, they are overturned to the north and have axial planes which dip gently to the south. The formation of third folds was such that northward-acting stress was rotated from southeast to southwest, and relaxation of this stress resulted in the development in competent strata of joints which strike at 120° and dip steeply. At the Lumwana Prospect the northward-acting Lufilian stress is thought to have been resolved into eastward acting stress during first and second folding as a result of compression near the centre of the Lufilian Arc. The third folds are the normal Lufilian folds sub-parallel to the Lufilian Arc. Normal faulting and intrusion of gabbro along planes of these faults and the earlier thrust faults eccurred in a post-Lufilian tensional phase. In recent times warping of the formations at Lumwana has occurred on east-west axes. Statistical examination of chemical data on fifty-four composite samples of mineralized rock from drill-holes reveals that the distribution of copper, iron and sulphur is related to that of potash and soda. These relationships can be explained on sedimentological grounds since the examination of the distribution of soda and potash in these and other horizons yields no evidence of metasomatism in the mineralized horizon. Intrusive into the mineralized schists, though not found in the ore, are thin amphibolites and a large serpentinite which contains relict olivine and bronzite. This is the first recorded occurrence of ultrabasic rocks in the Lower Roan Group of the Katanga System in this part of Zambia. Study of all formations at the Lumwana Prospect reveals that they have been metamorphosed in the epidote-amphibolite facies of regional metamorphism. Mineral assemblages indicative of the amphibolite facies are found in sheared rocks, and metamorphism in competent parts of the Upper Roan-Mwashia has been confined to the greenschist facies. Temperatures of metamorphism are estimated to have been between 250° and 280°C, and pressures are likely to have exceeded 6 kilobars. Evidence of metasomatism, absent in the Lower Roan, is found in the examination of the Upper Roan-Mwashia formations. Metasomatism includes scapolitization and albitization and is related to the intrusion of gabbro into these sediments, but does not necessarily involve exogenous material. The sulphide minerals identified are bornite, chalcocite, digenite, covellite, chalcopyrite, cubanite, valleriite, carrollite, pyrite and pyrrhotite. Intergrowths of these minerals have resulted from metamorphism at temperatures slightly in excess of 235°C. The copper sulphides are distributed zonally in the orebody with chalcocite- bornite ore where the mineralized schist is thin, and chalcopyrite- cubanite-pyrite ore where it is thick. Vertically the body contains horizons with sulphides relatively rich in copper at the top and bottom, and an intermediate zone with sulphides leaner in copper. This zonal distribution is considered to be evidence for syngenetic deposition of copper during successive cycles of transgression and regression. Ore genesis at Lumwana is closely related to genesis of the Copperbelt and Katanga orebodies. The Zambia-Katanga province is considered to have been enriched in copper epigenetically prior to the formation of the present-day orebodies. Reworking of these cupriferous rocks and some early-formed syngenetic deposits of which Lumwana is one, is considered to have played a major role in producing the present-day copper orebodies.
Keywords: Copper -- Zambia; Copper ores -- Zambia -- Analysis; Copper mines and mining -- Zambia; Mineralogy -- Zambia; Geology, Economic -- Zambia